MUSIC AND MUSIC AND PSYCHOLOGY: संगीत और मनोविज्ञान - Dudhale, Khaleda (International Journal of Research -GRANTHAALAYAH, 2015)
Music is a branch of psychology and musicology that aims to understand and explain musical behavior and musical experiences. At the same time, understanding how music is composed and how it reacts and how individuals adopt it in daily life. The psychology of morden music analyzes man's involvement with systemic observation. Its many areas are research and experimentation with execution (chamatvitundam) composition, education, criticism, medicine, etc. Music psychology helps in understanding social behavior by human intelligence, skill and functionality. संगीत मनोविज्ञान एवं संगीत शास्त्र की एक शाखा है जिसका लक्ष्य है संगीत व्यवहार और संगीत के अनुभवों को समझना और समझाना। साथ ही साथ यही समझना कि संगीत कैसे रचा जाता है और उसकी प्रतिक्रिया कैसी होती है और व्यक्ति उसे दैनिक जीवन में कैसे अपनाते है? माॅर्डन संगीत का मनोविज्ञान सिस्टेमेटिक अवलोकन से मनुष्य की भागीदारी का विश्लेषण करता है। इसके अनेक क्षेत्र हैं शोध व प्रयोग के साथ निष्पादन (चमतवितउंदबम) कम्पोजिशन, शिक्षा, आलोचना, चिकित्सा आदि। संगीत मनोविज्ञान मानव की बुद्धि, कौशल व क्रियात्मकता से सामाजिक व्यवहार को समझने में मदद करती है।